Pedot:Pss Polymer-Based Heterojunction Emitter For Textured Monocrystalline Silicon Solar Cells - Rosle, Mohamad Aliff Asraff (2024)
This work investigates optical, surface morphological and electrical properties of p-type PEDOT:PSS emitter on n-type textured mono c-Si for solar cell application. The mono c-Si wafers are textured using sodium hydroxide (NaOH) solution to form random upright pyramids on the surface. The parameter change involves concentration of NaOH (1%-3%), texturing temperature (70oC-90oC) and texturing time (40 min-60 min). The best sample is 2% NaOH for 50 min at 80oC, which results in weighted average reflection (WAR) of 18.06%.